Chlamydiaceae in wild, feral and domestic pigeons in Switzerland and insight into population dynamics by Chlamydia psittaci multilocus sequence typing. - Prisca Mattmann; Hanna Marti; Nicole Borel; Martina Jelocnik; Sarah Albini; Barbara Renate Vogler (PLoS ONE)
Feral pigeons, common wood pigeons and Eurasian collared doves are the most common representatives of the Columbidae family in Switzerland and are mostly present in highly populated, urban areas. Pigeons may carry various members of the obligate intracellular Chlamydiaceae family, particularly Chlamydia (C.) psittaci, a known zoonotic agent, and C. avium. The objective of the study was to identify the infection rates of common free-roaming pigeons for different Chlamydia species with the overall aim to assess the risk pigeons pose to public health. In this study, 431 pigeons (323 feral pigeons, 34 domestic pigeons, 39 Eurasian collared doves, 35 common wood pigeons) from several geographic locations in Switzerland were investigated for the presence of Chlamydiaceae. Samples consisted of pooled choanal-cloacal swabs (n = 174), liver samples (n = 52), and paired swab and liver samples from 205 pigeons (n = 410). All 636 samples were screened using a Chlamydiaceae family-specific 23S rRNA real-time PCR (qPCR). Subsequent species identification was performed by DNA-microarray assay, sequencing of a 16S rRNA gene fragment and a C. psittaci specific qPCR. In total, 73 of the 431 pigeons tested positive for Chlamydiaceae, of which 68 were positive for C. psittaci, four were C. avium-positive and one pigeon was co-infected with C. avium and C. psittaci. The highest infection rates were detected in feral (64/323) and domestic pigeons (5/34). Common wood pigeons (2/35) and Eurasian collared doves (2/39) revealed lower infection rates. Additionally, multilocus sequence typing of twelve selected C. psittaci-positive samples revealed closely related sequence types (ST) between and within different Swiss cities. Furthermore, liver and corresponding swab samples from the same bird were colonized by the same ST. Considering the high infection rates of C. psittaci in domestic and feral pigeons, close or frequent contact to these birds poses a human health risk.